The protective effect of hibiscus sabdariffa towards liver toxicity - Ahmad Raus, Raha; Mohd-Isa, Emy Sazri (2007)
This study was carried out to investigate the effect of Hibiscus sabdariffa or roselle on the progression of acute liver injury in rats. The liver injury was induced by administration of 1000 mg/kg acetaminophen intraperitoneally and aqueous extract at low (500 mg/kg) and high (1000 mg/kg) doses of H. sabdariffa was given to rats by force feeding. H. sabdariffa in the diet showed no significant effect on the liver marker enzymes, alanin transaminase (ALT) plus malonaldehyde (MDA) and reduced glutathione (GSH) except for glutathione S-transferase (GST). Interestingly, increased levels of ALT, GST and MDA plus significant reduction of GSH in acetaminophen treated rats were counteracted by the administration of H. sabdariffa. The effect of H. sabdariffa is dose-dependent as higher administrative dose of the plant extract to the acetaminophen treated rats resulted in further liver protective effects. Histopathologically H. sabdariffa reduced the incidence of liver damage. This study showed that the aqueous extract of H. sabdariffa had significant protective effect towards hepatotoxicity.